(untitled) (Colloquia Comparativa Litterarum, 2025)
In this study, reflection on bilingualism and bilingual writers leads to the didactics of language learning. The question of the imaginations of languages is at the heart of this research, which first gives voice to literature and then to pedagogical experience in order to reach a general conclusion on the cohabitation between languages and peoples.